2015
DOI: 10.5371/hp.2015.27.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiologic Outcomes among Bipolar Hemiarthroplasty, Compression Hip Screw and Proximal Femur Nail Antirotation in Treating Comminuted Intertrochanteric Fractures

Abstract: PurposeIn comminuted intertrochanteric fractures, various operative options have been introduced. The purpose of this study was to determine whether there were differences in clinical and radiologic outcomes among bipolar hemiarthroplasty (BH), compression hip screw (CHS) and proximal femur nail antirotation (PFNA) in treating comminuted intertrochanteric fractures (AO/OTA classification, A2 [22, 23])Materials and MethodsWe retrospectively evaluated total 150 patients (BH, 50; CHS, 50; PFNA, 50) who were opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 25 publications
0
34
0
1
Order By: Relevance
“…There were 19 studies that used cemented stem, 14 that used cementless stem, and two comparative studies that used both stems. Eleven studies were prospective studies, which used methods with wires, cables, and sutures for fixation of fracture fragments 1 2 4 11 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 19 studies that used cemented stem, 14 that used cementless stem, and two comparative studies that used both stems. Eleven studies were prospective studies, which used methods with wires, cables, and sutures for fixation of fracture fragments 1 2 4 11 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42) .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 comparative studies included an assessment of deep surgical site infection rates, of which eight used cemented stems 1 11 17 18 19 20 21 22) ; the remaining 10 used cementless stems 2 25 26 27 30 31 32 33 34 35) . There was low evidence of heterogeneity across the studies (I 2 =0%; P =0.999) leading to the use of a fixed model.…”
Section: Resultsmentioning
confidence: 99%
“…Radiologic shortening by stem subsidence could arise physiologically during fracture healing. 24 , 38 Munro et al reported that subsidence was observed in 24% of patients, although the majority of cases were less than 3 mm, and only 9% subsided more than 3 mm. 25 Mulay et al reported a mean subsidence of 5 mm (range, 2–10 mm) in 17 of 24 patients 48.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, all cases achieved bony union without notable complications that would have required additional surgery, except 1 patient of refracture at the distal tip of plate. Radiologic shortening by stem subsidence could arise physiologically during fracture healing 24, 38. Munro et al reported that subsidence was observed in 24% of patients, although the majority of cases were less than 3 mm, and only 9% subsided more than 3 mm 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The complex three-dimensional anatomy of bone dislocation is difficult to assess, which may lead to a prolonged period of traction reduction and radiation exposure ( 14 ). Furthermore, the severe displacement of ITF fragments may make closed reduction and internal fixation prone to varus/vague deformities ( 15 ).…”
Section: Introductionmentioning
confidence: 99%